Access to finance and difference in family farm productivity in Benin: Evidence from small farms - Denis Acclassato Houensou; Godefroy G. Goudjo; Melain Modeste Senou, PhD (Scientific African, 2021)
In most of developing countries, agricultural finance is weak and there is a great constraint for family farmers to access credit. In that context, this article aims to analyze the effect of access to finance on the productivity of smallholders family farmers. Using a rich national representative survey data covering the 2016–2017 agricultural season, we estimated an Endogenous Switching Regression (ESR) model. The results show that access to credit has a positive impact on the productivity of smallholder farmers, with a gain of 15%. Small farmers manage to achieve a 13% increase in productivity, which is a very significant performance. These findings suggest the establishment of a policy to support small farms, so that they are more productive and more favorable to agricultural growth.